Quality characteristics of biscuits supplemented with mango kernel and sugar beet molasses ingredients (Romanian Biotechnological Letters, 2024)
Mango kernel is largely treated as a waste material, but its flour can be used in many foods as a potential replace of wheat flour (WF). Sugar beet molasses (SBM) is a raw material with high possibility to be a functional ingredient in baked commodities. The aims of this research were to process mango kernel flour (MAKF) and sugar beet molasses (SBM) to comparison its chemical composition and minerals content and really to evaluate the quality of MAKF and SBM  substituted composite biscuits by investigating chemical composition, minerals content, physical and textural characteristics and sensory evaluation of produced biscuits. The composition of MAKF and SBM showed higher concentration of ash (6.97 and 10.62%, respectively) compared to WF. MAKF showed higher amounts of  fat and fiber than WF (3.22 and 2.34%, respectively). Moisture and ash contents of the developed biscuits increased with increasing of MAKF and SBM contents. MAKF increased all minerals content in the all prepared biscuits, while SBM caused an increase only in Na and Fe. Sensory evaluation indicated that 5% SBM and 10% MAKF containing biscuit were the most acceptable to the panelists among composite biscuits.
Keywords: Mango kernel flour; Sugar beet molasses; Composite biscuit; Textural characteristics; Physical properties